Asymmetric two-dimensional metal organic framework membrane as well as preparation and separation application thereof

By performing functional group gradient regulation and multi-step preparation technology on organic ligands, high-quality two-dimensional metal organic framework micro-region asymmetric membrane was prepared, which solved the problems of membrane structure regulation and interface compatibility in the prior art, and achieved efficient gas and liquid phase separation performance.

CN119607909AActive Publication Date: 2025-03-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311174152.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

It is difficult to achieve fine regulation of the specified regional structures, and the introduction of new phases may lead to poor interfacial compatibility, limiting the preparation and application of high-quality two-dimensional metal organic framework micro-region asymmetric membranes.

Method used

By controlling the modulation of the organic ligands, introducing different functional groups, controlling the modification of the chemical properties of the membrane material, and using solvent thermal synthesis, ultrasonic dispersion, porous carrier assembly and microwave-assisted secondary growth methods to prepare two-dimensional metal organic framework micro-region asymmetric membrane.

Benefits of technology

The performance of two-dimensional ultra-thin films has been optimized, and the separation performance of hydrogen/carbon dioxide and ethanol dehydration has been improved, and the performance of good gas screening and liquid phase separation is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004444983630000051
    Figure BDA0004444983630000051
  • Figure BDA0004444983630000061
    Figure BDA0004444983630000061
  • Figure HDA0004444983640000011
    Figure HDA0004444983640000011
Patent Text Reader

Abstract

The invention discloses an asymmetric two-dimensional metal organic framework membrane as well as a preparation method and separation application thereof. The organic ligand is controllably modulated, and different functional groups are introduced, so that the separation performance of hydrogen / carbon dioxide and ethanol dehydration is improved. The preparation method comprises the following steps: synthesizing precursor nanosheets by a solvothermal method, peeling to obtain a two-dimensional nanosheet dispersion liquid, assembling the nanosheets on the surface of a porous carrier, and carrying out microwave-assisted secondary growth to form the film. The two-dimensional metal organic framework microcell asymmetric membrane prepared through a functional group gradient regulation strategy has excellent gas screening and liquid phase separation performance and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane separation and relates to an asymmetric two-dimensional metal organic framework membrane and its preparation and separation application. Background Art

[0002] Separation is an indispensable process in modern chemical industry. Membrane separation technology has the advantages of low energy consumption, continuous operation and environmental friendliness. It has been widely used in gas separation, water resource treatment, catalysis, sensing and other fields. The rapid development and wide application of membrane separation technology have important practical significance for my country to achieve the goal of "carbon peak and carbon neutrality". Membrane materials are the basis and core of membrane separation technology. Metal-organic frameworks are porous crystal structures formed by metal ions or metal clusters and organic ligands connected by coordination bonds. They have the advantages of rich skeleton structure, ultra-high relative surface area and porosity, rich pore structure and surface chemical properties. The high separation performance of metal-organic framework materials after film formation usually depends on the precise microstructure of the membrane. However, the existing membrane structure regulation strategies usually have the problem of difficulty in achieving fine regulation of the structure of the specified area, and the introduction of new phases may result in poor interface compatibility. Therefore, in view of the problem that most membrane structures in current research have microscopic phase interfaces, high-quality two-dimensional metal-organic framework micro-region asymmetric membranes are prepared, and their excellent performance of high selectivity and high permeability is expected to achieve precise and efficient separation in large-scale application scenarios. Summary of the invention

[0003] The purpose of the present invention is to provide an asymmetric two-dimensional metal organic framework membrane and its preparation method and application, which is a method for controllably modifying the chemical properties of membrane materials by controllably adjusting organic ligands and introducing different functional groups, and performing gas separation and liquid phase separation performance tests on the obtained ultra-thin micro-area asymmetric membrane material to improve its hydrogen / carbon dioxide and ethanol dehydration separation performance.

[0004] A method for preparing an asymmetric two-dimensional metal organic framework membrane, using solvent thermal synthesis of precursor metal organic framework nanosheets, obtaining a nanosheet suspension after ultrasonic dispersion, then assembling it on a porous carrier, and then performing microwave-assisted secondary growth to obtain a two-dimensional metal organic framework micro-area asymmetric membrane. The specific preparation process includes the following steps:

[0005] (1) Solvothermal method for synthesizing sheet precursor materials: trivalent aluminum salt is selected as the metal source, and trivalent aluminum salt, organic ligand, hexadecyltrimethylammonium bromide, tetramethylammonium hydroxide and water are mixed and reacted at 30-200°C for 0.1-48h to obtain a two-dimensional sheet metal organic framework precursor;

[0006] Among them, the molar ratio of each raw material is Al 3+: Organic ligand: hexadecyltrimethylammonium bromide: tetramethylammonium hydroxide: water = 0.01-5: 0.01-5: 0.01-5: 1-10: 1-10000;

[0007] (2) Preparation of a two-dimensional lamellar nanosheet dispersion: mixing the two-dimensional lamellar metal organic framework precursor obtained in step (1) with a solvent, obtaining a two-dimensional nanosheet dispersion by exfoliation, and allowing the dispersion to settle for 1-300 days;

[0008] The peeling method includes grinding, ultrasonic dispersion, ball milling, freeze-thaw and other methods; the mass concentration of the two-dimensional nanosheets in the obtained nanosheet dispersion is 0.001-1%;

[0009] (3) assembling two-dimensional nanosheets: assembling the nanosheet dispersion obtained in step (2) onto the surface of a porous carrier at room temperature, and drying the dispersion to obtain a porous carrier carrying a two-dimensional metal organic framework nanosheet seed layer;

[0010] When preparing a porous carrier carrying a two-dimensional metal organic framework nanosheet seed layer, the assembly amount of the two-dimensional layered nanosheet dispersion is 1 to 100 mL / cm 2 Carrier;

[0011] (4) Preparation of a two-dimensional metal organic framework micro-domain asymmetric membrane: placing the porous carrier (two-dimensional metal organic framework nanosheet seed layer) loaded with seeds obtained in step (3) in a secondary growth solution, reacting at a certain temperature for an appropriate time by microwaves, and then washing and drying to obtain a two-dimensional metal organic framework micro-domain asymmetric membrane;

[0012] The secondary growth solution is a mixed solution of trivalent aluminum salt, organic ligand, tetramethylammonium hydroxide and water, and the molar ratio of each raw material is: Al 3+ :Organic ligand:tetramethylammonium hydroxide:water=0.01~10:0.01~10:1~10:1~5000;;

[0013] In step (1) and step (4), the types of organic ligands are different.

[0014] Based on the above technical scheme, preferably, in step (1) and step (4), the trivalent aluminum salt is at least one of aluminum sulfate 18hydrate, aluminum chloride hexahydrate, and aluminum nitrate nonahydrate; and the organic ligand is at least one of isophthalic acid, 5-aminoisophthalic acid, 5-bromoisophthalic acid, 5-hydroxyisophthalic acid, and 5-nitroisophthalic acid, or a mixture of several thereof.

[0015] Based on the above technical solution, preferably, in step (1), the reaction temperature is 60-150 degrees Celsius and the reaction time is 10-36 hours.

[0016] Based on the above technical solution, preferably, in step (1), the raw material ratio is Al 3+ : Organic ligand: hexadecyltrimethylammonium bromide: tetramethylammonium hydroxide: water = 1.5-3.5: 1.5-3.5: 0.5-1: 1-5: 1000-1500.

[0017] Based on the above technical solution, preferably, in step (2), the solvent includes an organic solvent (the organic solvent is one or a mixture of methanol, ethanol, acetone, tetrahydrofuran, N, N-dimethylformamide), one or a mixture of water. Based on the above technical solution, preferably, in step (2), the ultrasonic dispersion conditions are ultrasonic 0.1-4h, and the power is 200-500W.

[0018] Based on the above technical solution, preferably, in step (2), the static sedimentation is more than 7 days and less than 300 days.

[0019] Based on the above technical solution, preferably, in step (2), the static sedimentation is more than 14 days and less than 100 days.

[0020] Based on the above technical scheme, preferably, in step (3), the porous carrier (base membrane) is at least one of porous alumina, anodized aluminum oxide, silicon nitride, polytetrafluoroethylene, polyvinylidene fluoride, polyethersulfone, polyacrylonitrile, and stainless steel, preferably one of α-Al2O3 carrier, γ-Al2O3 carrier, stainless steel carrier, and polytetrafluoroethylene; the pore size of the porous carrier is 5nm-10μm, preferably 5nm~1μm.

[0021] Based on the above technical solution, preferably, in step (3), the porous carrier is in the shape of a sheet structure, a fiber structure or a tubular structure.

[0022] Based on the above technical solution, preferably, in step (3), the drying conditions are: drying temperature 30-120° C., and drying time 1-24 h.

[0023] Based on the above technical solution, preferably, in step (3), the nanosheet assembly method includes at least one of suction filtration, hot drop coating, spin coating, and dip-pulling.

[0024] The filtration is a vacuum filtration method, and the vacuum assembly is performed at room temperature of 0 to -0.1 MPa; the hot drop coating method is a hot drop assembly at 100-150°C; and the amount of the nanosheet dispersion used is 1-15 mL per unit area of ​​the carrier.

[0025] Based on the above technical solution, preferably, in step (4), the molar ratio of the raw materials of the secondary growth solution is: Al 3+: Organic ligand: tetramethylammonium hydroxide: water = 1-3: 1-3: 1-5: 1000-1500.

[0026] Based on the above technical scheme, preferably, in step (4), the heating rate is 0.5-20°C / min, preferably 1-15°C / min; the power is 1-900 watts, preferably 200-400 watts; the reaction temperature is 30-120°C, preferably 80-120°C; and the reaction time is 1-240min, preferably 15-180min.

[0027] Based on the above technical solution, preferably, in step (4), the solvent used for rinsing is at least one of water, methanol, ethanol and acetone, the drying temperature is 30-120° C., and the drying time is 1-24 h.

[0028] The present invention also relates to an asymmetric two-dimensional metal organic framework film prepared by the method described above.

[0029] The present invention also relates to the application of the asymmetric two-dimensional metal organic framework membrane described above in gas separation and liquid separation, especially hydrogen / carbon dioxide separation and ethanol dehydration separation.

[0030] Beneficial effects: The present invention first synthesizes a sheet precursor by a solvothermal method, then peels off the layers to obtain a two-dimensional nanosheet dispersion, then orderly assembles them on the surface of a porous carrier, and finally obtains a two-dimensional metal organic framework micro-area asymmetric membrane by microwave-assisted secondary growth. By selecting organic ligands, functional groups with different chemical properties are introduced into the skeleton to gradient-regulate the chemical properties of the membrane material for controllable modification, thereby optimizing the performance of the two-dimensional ultra-thin film. The two-dimensional metal organic framework micro-area asymmetric membrane prepared by the functional group gradient control strategy of the present invention has excellent gas screening and liquid phase separation performance, and has good application prospects in the fields of gas separation and liquid phase separation, especially the separation of hydrogen / carbon dioxide and ethanol dehydration. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention is attached Figure 7 The widths are:

[0032] Figure 1 This is the X-ray diffraction pattern of the CAU-10-H flake precursor material synthesized in Example 1;

[0033] Figure 2 This is a scanning electron microscope photo of the CAU-10-H flake precursor material synthesized in Example 1;

[0034] Figure 3 This is a scanning electron microscope photo of the CAU-10-H nanosheet dispersion material synthesized in Example 2;

[0035] Figure 4This is a scanning electron microscope photo of the ordered assembly material of CAU-10-H nanosheets synthesized in Example 3;

[0036] Figure 5 This is the X-ray diffraction pattern of the CAU-10-H pure phase membrane material synthesized in Example 4;

[0037] Figure 6 This is a scanning electron microscope photo of the CAU-10-H pure phase membrane material synthesized in Example 4;

[0038] Figure 7 This is a scanning electron microscope photograph of the CAU-10-H / OH micro-area asymmetric membrane material synthesized in Example 5. DETAILED DESCRIPTION

[0039] The present invention will be further described in the following examples, but the present invention is not limited thereto.

[0040] Example 1 Preparation of CAU-10-H sheet precursor

[0041] Dissolve 1.1 g of aluminum nitrate nonahydrate and 0.8 g of hexadecyltrimethylammonium bromide in 15 ml of pure water to obtain a mixed solution 1; dissolve 0.4 g of isophthalic acid in 4 ml of tetramethylammonium hydroxide and 10 ml of pure water, stir for 5 minutes and preheat, then mix it with the mixed solution 1 and put it into a 100 ml reactor, place it in an oven, react at 100 degrees Celsius for 20 hours, take out the reactor and cool to room temperature. The CAU-10 flake precursor obtained by centrifugation is repeatedly washed with water and ethanol, and the product is dried in an oven at 100 degrees Celsius overnight.

[0042] X-ray diffraction confirmed that the product had a CAU-10 structure (e.g. Figure 1 ), proving that the flake precursor material was successfully synthesized. Scanning electron microscope images show that the product has a distinct flake morphology (such as Figure 2 ).

[0043] Example 2 Preparation of CAU-10-H Nanosheet Dispersion

[0044] 50 mg of the CAU-10 precursor material prepared in Example 1 was dispersed in 500 ml of ethanol, and ultrasonically stripped at a power of 300 watts for 30 minutes, and allowed to stand for more than 14 days for use.

[0045] Scanning electron microscope images show that the product has a distinct flake morphology (such as Figure 3 ).

[0046] Example 3 Assembly of CAU-10-H nanosheets

[0047] A porous α-Al2O3 carrier (diameter 18 mm) with a pore size of 70 nm was placed in a suction filtration device, and 10 ml of the nanosheet dispersion in Example 2 was taken and assembled in an orderly manner under a pressure of -0.08 MPa, and then placed in an oven at 100 degrees Celsius to dry overnight.

[0048] Scanning electron microscope images show successful assembly of nanosheets (e.g. Figure 4 ).

[0049] Example 4 Preparation of CAU-10-H Pure Phase Membrane

[0050] 0.75 g of aluminum nitrate nonahydrate and 0.25 g of isophthalic acid were added to a mixed solution of 3 ml of tetramethylammonium hydroxide and 20 ml of water, stirred evenly, and placed in the porous alumina loaded with nanosheets in Example 3, and reacted for 120 minutes at 100 degrees Celsius (heating to 100 degrees Celsius at a heating rate of 15 degrees Celsius / min) in a microwave reactor with a power of 400 watts. After the reactor was taken out and cooled to room temperature, the membrane surface was rinsed with water and methanol in turn, and then dried in an oven at 100 degrees Celsius overnight.

[0051] X-ray diffraction confirmed the formation of film structure and its orientation (e.g. Figure 5 ). Scanning electron microscopy images show that the product has a dense and continuous morphology (such as Figure 6 ).

[0052] Example 5 Preparation of CAU-10-H / OH Microdomain Asymmetric Membrane

[0053] The isophthalic acid in Example 4 was replaced with an equal molar amount of 5-hydroxyisophthalic acid, and the remaining reaction steps were the same. Aluminum nitrate nonahydrate and 5-hydroxyisophthalic acid were added to a mixed solution of tetramethylammonium hydroxide and water, stirred evenly, and the porous alumina loaded with nanosheets in Example 3 was added, and the reaction was carried out in a microwave reactor at 100 degrees Celsius (heated to 100 degrees Celsius at a heating rate of 15 degrees Celsius / min) for 120 minutes, with a power of 400 watts. After the reactor was taken out and cooled to room temperature, the membrane surface was rinsed with a mixed solution of methanol and water, and then dried in an oven at 100 degrees Celsius overnight.

[0054] Scanning electron microscopy images show that the product has a dense and continuous morphology (such as Figure 7 ).

[0055] Example 6 Preparation of CAU-10-H / NH2 Micro-Asymmetric Membrane

[0056] The isophthalic acid in Example 4 was replaced by an equal mole of 5-aminoisophthalic acid, and the remaining reaction steps were the same.

[0057] Example 7 Preparation of CAU-10-H / Br micro-area asymmetric membrane

[0058] The isophthalic acid in Example 4 was replaced by an equal mole of 5-bromoisophthalic acid, and the remaining reaction steps were the same.

[0059] Example 8 Hydrogen / Carbon Dioxide Gas Separation Test of Two-Dimensional Metal-Organic Framework Membrane

[0060] The two membranes prepared in Examples 4-5 were packaged in a Wicke-Kallenbach membrane module and tested for separation of a hydrogen / carbon dioxide mixed gas at room temperature and ΔP = 0 MPa, with argon as the purge gas. (Under standard conditions, 1 GPU = 1 × 10 -6 cm 3 / cm 2 ·s·cmHg). Three sheets of each membrane in Examples 4-5 were prepared for performance testing. The data in the table show that compared with the pure phase membrane, the micro-domain asymmetric membrane obtained by introducing a hydroxyl-containing ligand for secondary growth can improve the gas separation performance of the membrane material by using a chemical modification method in which the hydroxyl group in the micro-domain changes from presence to absence.

[0061] serial number <![CDATA[H2 / CO2 separation factor]]> <![CDATA[H2 Permeation (GPU)]]> <![CDATA[CO2 Permeation Rate (GPU)]]> CAU-10-H pure phase membrane 1 98 720 7.35 CAU-10-H pure phase membrane 2 112 736 6.57 CAU-10-H pure phase membrane 3 106 816 7.70 CAU-10-H / OH micro-domain asymmetric membrane 1 248 642 2.59 CAU-10-H / OH micro-domain asymmetric membrane 2 209 690 3.30 CAU-10-H / OH micro-domain asymmetric membrane 3 256 603 2.36

[0062] Example 9 Alcohol-water liquid phase separation test of two-dimensional metal organic framework membrane

[0063] The separation performance of the two membranes prepared in Examples 4-5 for ethanol dehydration was evaluated in the pervaporation process. Three membranes of each type in Examples 4-5 were prepared for performance testing. The test was conducted at 65°C by preparing a mixed solution of alcohol and water containing 90% ethanol. The measured performance is shown in the following table:

[0064]

[0065]

Claims

1. A method for preparing an asymmetric two-dimensional metal organic framework membrane, characterized in that: The steps include: (1) mixing trivalent aluminum salt, organic ligand, hexadecyltrimethylammonium bromide, tetramethylammonium hydroxide and water, and reacting at 30-200° C. for 0.1-48 hours to obtain a two-dimensional sheet-like metal organic framework precursor; Among them, the molar ratio of each raw material is Al 3+ : Organic ligand: hexadecyltrimethylammonium bromide: tetramethylammonium hydroxide: water = 0.01-5: 0.01-5: 0.01-5: 1-10: 1-10000; (2) mixing the precursor of the two-dimensional sheet-like metal organic framework obtained in step (1) with a solvent, peeling the layers to obtain a nanosheet dispersion, and allowing it to settle for 1 to 300 days; Wherein, the mass concentration of the two-dimensional nanosheets in the nanosheet dispersion is 0.001-1%; (3) assembling the nanosheet dispersion obtained in step (2) onto the surface of a porous carrier at room temperature, and drying the nanosheet dispersion to obtain a porous carrier carrying a two-dimensional metal organic framework nanosheet seed layer; When preparing a porous carrier carrying a two-dimensional metal organic framework nanosheet seed layer, the assembly amount of the two-dimensional layered nanosheet dispersion is 1 to 100 mL / cm 2 Carrier; (4) placing the porous carrier carrying the two-dimensional metal organic framework nanosheet seed layer obtained in step (3) in a secondary growth solution, reacting it at a certain temperature for a certain time by microwaves, and then washing and drying to obtain a two-dimensional metal organic framework micro-domain asymmetric membrane; The secondary growth solution is a mixed solution of trivalent aluminum salt, organic ligand, tetramethylammonium hydroxide and water, and the molar ratio of each raw material is: Al 3+ : Organic ligand: tetramethylammonium hydroxide: water = 0.01-10: 0.01-10: 1-10: 1-5000; In step (1) and step (4), the types of organic ligands are different.

2. The preparation method according to claim 1, characterized in that: In step (1) and step (4), the trivalent aluminum salt is at least one of aluminum sulfate 18hydrate, aluminum chloride hexahydrate, and aluminum nitrate nonahydrate; the organic ligand is at least one of isophthalic acid, 5-aminoisophthalic acid, 5-bromoisophthalic acid, 5-hydroxyisophthalic acid, 5-nitroisophthalic acid, 5-methylisophthalic acid, 5-methoxyisophthalic acid, and 5-fluoroisophthalic acid; and the tetramethylammonium hydroxide is a 25% tetramethylammonium hydroxide aqueous solution.

3. The preparation method according to claim 1, characterized in that: In step (2), the solvent includes one or a mixture of methanol, ethanol, acetone, tetrahydrofuran, N,N-dimethylformamide, and water; and the stripping method includes at least one of grinding, ultrasonic dispersion, ball milling, and freeze-thaw.

4. The preparation method according to claim 1, characterized in that: In step (3), the porous carrier used is at least one of porous alumina, anodized aluminum oxide, silicon nitride, polytetrafluoroethylene, polyvinylidene fluoride, polyethersulfone, polyacrylonitrile, and stainless steel, and the pore size is 5nm-10μm; the porous carrier is in the shape of a sheet, fiber or tubular structure.

5. The preparation method according to claim 1, characterized in that: In step (3), the drying temperature is 30-120° C. and the drying time is 1-24 h.

6. The preparation method according to claim 1, characterized in that: In step (3), the nanosheet assembly method includes at least one of suction filtration, hot drop coating, spin coating, and dip-pulling.

7. The preparation method according to claim 1, characterized in that: In step (4), the conditions of the microwave reaction are: a heating rate of 0.5-20°C / min, a power of 1-900 watts, a reaction temperature of 60-150°C, and a reaction time of 1-240 min.

8. The preparation method according to claim 1, characterized in that: In step (4), the solvent used for washing is at least one of water, methanol, ethanol and acetone, the drying temperature is 30-120° C., and the drying time is 1-24 hours.

9. An asymmetric two-dimensional metal organic framework membrane prepared by the method according to any one of claims 1 to 8.

10. Use of the asymmetric two-dimensional metal organic framework membrane described in claim 9 in gas separation and liquid separation.

Citation Information

Patent Citations

  • Preparation method and application for two-dimensional metal organic framework nanosheet

    CN110387049A

  • Two-dimensional metal organic framework nanosheet film and preparation method and application thereof

    CN112973456A

  • Preparation method of defect-free pollution-resistant zirconium-based metal organic framework membrane and application thereof

    CN113041863A

  • Preparation method and application of self-supporting bifunctional membrane material based on aluminum-based heterogeneous nanosheets

    CN116190617A

  • Preparation method of two-dimensional metal organic framework gas separation membrane material

    CN116262206A